THE NEED TO INCREASE THE INDEPENDENCE OF LOCAL BUDGETS IN UZBEKISTAN - Sharapova Mashkhura Azadovna (American Journals, 2023)
This article highlights ways to strengthen the revenue base of local budgets while ensuring their independence, the distribution of budget revenues, including taxes, between the republican and local budgets while ensuring their independence, the distribution of budget revenues, including taxes, between the republican and local budgets while ensuring the sustainability of local budgets.
Keywords: local budgets, independence of local budgets, revenues of local budgets, tax revenues, inter-budgetary distribution of budget transfers.